2015
DOI: 10.1016/j.conbuildmat.2015.08.017
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of the GPR frequency spectra in asphalt pavement assessment

Abstract: Ground penetrating radar (GPR) is frequently used in pavement assessments, mainly using the evaluation of wave travel times. However, GPR data provide further information that could be used in order to determine the inner conditions and characteristics about materials. In this paper, the possible analysis of the frequency spectrum of GPR signals is analysed and discussed. Several tests were carried out in a portion of a highway in two different stages of its service life. Results highlight the relationship bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…In civil engineering, GPR is applied to map and locate utilities [7,8,9], monitor and inspect concrete structures for defects and anomalies in the service of civil infrastructure SHM and life-cycle management (e.g., [10]). Specifically, GPR has been used for damage identification in different ages and mixes of concrete [11], corrosion detection and prevention [12,13], robust estimates of pavement thickness [14,15,16] and identification of voids and other defects in civil structures [10,17]. Some work is being done on estimating and tracking the evolution of volumetric water content and dielectric properties, but mainly in the interest of understanding early age concrete hydration [18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…In civil engineering, GPR is applied to map and locate utilities [7,8,9], monitor and inspect concrete structures for defects and anomalies in the service of civil infrastructure SHM and life-cycle management (e.g., [10]). Specifically, GPR has been used for damage identification in different ages and mixes of concrete [11], corrosion detection and prevention [12,13], robust estimates of pavement thickness [14,15,16] and identification of voids and other defects in civil structures [10,17]. Some work is being done on estimating and tracking the evolution of volumetric water content and dielectric properties, but mainly in the interest of understanding early age concrete hydration [18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…For example, some researchers showed that non-destructive technologies are not able to identify debonding between asphalt layers because of an inadequate tack coat execution. However, GPR can be used to detect this distress when moisture is trapped in the interface [41,42]. In addition, some researchers discuss the ability of non-destructive technologies to detect an inadequate tack coat execution [41].…”
Section: Detection Of Failures In Pavementsmentioning
confidence: 99%
“…The spectrum is also sensible to clay content in the pavement base, and several studies point to the possibility of using the peaks displacement to detect changes in clay content [74]. The work of Pedret et al [42] analyses a section of flexible pavement by evaluating the changes in the spectrum according to the thickness of the bituminous mixture layers, the moisture and the detachment between layers. Based on the variations observed in the bandwidth and in the amplitude of the frequency spectrum maximums, the use of GPR is proposed to define stretches of road in accordance with the parameters observed in the frequency spectrum.…”
Section: The Frequency Spectrummentioning
confidence: 99%
See 1 more Smart Citation
“…The signal processing in frequency domain is a potential tool for detecting changes in the characteristics of the material tested, which is not limited to thickness only. It was applied at research level for detecting damage in airport pavements, using ground coupled antennas [7]. The application of this approach to the assessment of railway infrastructure is presented in this study as an example of possible infrastructure monitoring at the network level [8].…”
Section: Signal Processing In Frequency Domainmentioning
confidence: 99%